2023
DOI: 10.1038/s41598-023-36034-2
|View full text |Cite
|
Sign up to set email alerts
|

Combination of genetically diverse Pseudomonas phages enhances the cocktail efficiency against bacteria

Abstract: Phage treatment has been used as an alternative to antibiotics since the early 1900s. However, bacteria may acquire phage resistance quickly, limiting the use of phage treatment. The combination of genetically diverse phages displaying distinct replication machinery in phage cocktails has therefore become a novel strategy to improve therapeutic outcomes. Here, we isolated and studied lytic phages (SPA01 and SPA05) that infect a wide range of clinical Pseudomonas aeruginosa isolates. These relatively small myop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 23 publications
(15 citation statements)
references
References 87 publications
0
15
0
Order By: Relevance
“…To observe the progress of the replication cycle of the phage Callisto in comparison to the well-studied chimalliviruses PhiKZ, we performed a single-cell infection assay and observed DAPI-staining DNA to follow the phage reproduction process in the host cells. 41 , 52 The results showed that, during the phage infections, the infected Pseudomonas cells had their morphology altered throughout the time, which might be a result of the phage infections compared to the uninfected cell control ( Figures 3 A, 3C, and 3D). During infection with phage PhiKZ ( Figure 3 A; PhiKZ), the phage assembled the phage nucleus localized close to the midcell of the host ( Figure 3 A; PhiKZ, green arrows).…”
Section: Resultsmentioning
confidence: 98%
See 3 more Smart Citations
“…To observe the progress of the replication cycle of the phage Callisto in comparison to the well-studied chimalliviruses PhiKZ, we performed a single-cell infection assay and observed DAPI-staining DNA to follow the phage reproduction process in the host cells. 41 , 52 The results showed that, during the phage infections, the infected Pseudomonas cells had their morphology altered throughout the time, which might be a result of the phage infections compared to the uninfected cell control ( Figures 3 A, 3C, and 3D). During infection with phage PhiKZ ( Figure 3 A; PhiKZ), the phage assembled the phage nucleus localized close to the midcell of the host ( Figure 3 A; PhiKZ, green arrows).…”
Section: Resultsmentioning
confidence: 98%
“… 64 For example, utilizing genetically diverse phages that exhibit distinct mechanisms of pre-killing (MOK) is shown to be a superior approach compared to employing closely related phages or single phage alone. 41 In particular, our jumbophages Callisto and PhiKZ, which are proven here to display different MOKs, would possibly be potential candidates for an effective phage combination for further investigation of their use in clinical settings. It is worth noting that some jumbophages might have drawbacks for application due to their nature: a long latent period and small burst size, 27 , 28 and these factors should definitely be taken into account when selecting jumbophage candidates for therapy.…”
Section: Discussionmentioning
confidence: 93%
See 2 more Smart Citations
“…66 SPA01 and SPA05 phages were used to treat infection in vitro caused by P. aeruginosa, which showed phage resistance due to the prevention of phage adsorption and phage-host interaction, possibly via receptor modification by the host immune system or genetic modification. 67 In myophage, T4 spike protein gp5 is a lysozyme responsible for hydrolyzing glycosidic bonds in peptidoglycan, forming stable complexes along with the help of gp27 protein. 68 Phage encounters a restriction-modification (R-E) system which allows restriction endonuclease to cleave foreign genome.…”
Section: Challenges For Phage Therapy and Factors Affecting Its Succe...mentioning
confidence: 99%